1995
DOI: 10.1097/00003246-199512000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed therapy with dopexamine, dobutamine, and volume expansion

Abstract: Increasing cardiac output and VO2 before and during infection was only protective when dopexamine was administered. Dobutamine infusion was associated with greater hepatic deterioration than that effect seen in either the control or volume groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28]. An increase in stroke volume was mainly observed in studies using prolonged infusion (from 2 to 6 h) at doses higher than 10 µg/kg/min [6], [8], [9], [17].…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28]. An increase in stroke volume was mainly observed in studies using prolonged infusion (from 2 to 6 h) at doses higher than 10 µg/kg/min [6], [8], [9], [17].…”
Section: Resultsmentioning
confidence: 85%
“…Some found no changes in arterial blood pressure [7][9], [17], [20], [24], [28], but in a few studies the arterial blood pressure increased at the highest dose studied [6], [11], [19], [26], [27]. Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations